Laporan Kasus Karsinoma Sel Skuamosa yang Berkembang dari Papiloma Tipe Inverted Sinonasal pada Pekerja Pabrik Cermin - Riani, Fety; Marlita Sari, Ita (Sanus Medical Journal, 2022)
Background. Sinonasal inverted (PI) papilloma is a benign tumor of the mucosal epithelium of the nasal cavity and paranasal sinuses with an endophytic growth pattern. PI is more common in men in the fifth and sixth decades of life. These tumors have local aggressive behavior, high recurrence rates, and can undergo malignant transformation. Squamous cell carcinoma (SCC) is the most common malignancy developed from sinonasal PI. SSC developed from PI (KSS/PI) is related to exposure in the work environment. Methods. We report a sinonasal SCC/PI case by describing the clinical manifestations, radiological features, and histopathological features of a young male patient who was a non"‘smoker mirror"‘making factory worker. Results. Clinical manifestations of pain, epistaxis, and proptosis in patients suggest malignancy. Computed Tomography (CT) results showed lesions of the nasal cavity and paranasal sinuses with bone destruction and expansion of the mass to the intracranial point of the aggressive behavior of the tumor. Microscopic histopathological examination revealed endophytic squamous epithelial growth characteristic of an inverted papilloma accompanied by cell atypia, invasive components, connective tissue desmoplasia, and keratin pearls, suggesting a well"‘differentiated keratinized squamous cell carcinoma that developed from the sinonasal inverted papilloma. Exposure to dust in the work environment is related to malignancy in this patient. Conclusion. Support of clinical and radiological data, adequate sampling, and identification of malignancy morphology routinely on histopathological examination is critical to avoid misdiagnosis of sinonasal SCC/PI. A complete history directed at extracting risk factors can add value in establishing a diagnosis.